SOGLIE MOBILI: TITOLI CAMBIATI E STRATEGIE EDITORIALI NEL ROMANZO ROMENO SOTTO IL REGIME COMUNISTA (Analele Universității București. Limba și literatură română, 2025)
The article analyses title changes in Romanian novels written between 1948 and 1989, a period defined by the establishment and consolidation of the communist regime. Using data from Dicționarul cronologic al romanului românesc de la origini până la 2000 (DCRR), the study examines how title changes indicate the evolving dynamics of the literary field under ideological control. Rather than examining the relationship between titles and their designated texts, the focus is on the process that led to these modifications, revealing the constant negotiation between authorial intent, ideological constraints, and editorial strategies. Title modifications are classified into two main categories: those introduced in later editions or reprints, and those made before the first publication of a novel. These paratextual interventions, which are often influenced by changing political and cultural contexts, demonstrate the adaptability of the paratext, as theorized by Gérard Genette, as a transitional space that mediates between the ‘ideal identity’ of the work and the socio-historical reality of its audience.
Keywords: Romanian novel; paratexts; titles; communism; censorship